Training, abilities and the structure of teams - Tobias Hiller (Games, 2023)
Training in firms has an effect on the productivity of employees who receive the training, and depending on the production technology, on the other employees as well. Meanwhile, changing the remuneration structure within a team can change the stability of a team. In this paper, we apply the production games approach of cooperative game theory to analyze how training employees affects the stability of team structures and employee wages. Concretely, we apply coalition structures and the 𝜒 value. Our results are in line with the literature and numerous further research questions can be addressed based on our approach.
Keywords: C71; D21; J24; 330; production games; abilities; structure of teams; training